2013
DOI: 10.1016/j.jpeds.2012.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Insulin Sensitivity and Cardiovascular Disease Risk Factors in Adolescents with and without Type 1 Diabetes

Abstract: Objective To test the hypothesis that cardiovascular disease (CVD) risk factors are similar in adolescents with and without diabetes (T1D) in the most insulin sensitive (IS) tertile and CVD risk factors are more atherogenic with decreasing IS in adolescents with T1D. Study design Adolescents with IS T1D (n=292; age=15.4±2.1 years; duration=8.8±3.0 years, HbA1c=8.9±1.6%) and non-diabetic (non-DM) controls (n=89; age=15.4±2.1 years) was estimated using the model: logeIS=4.64725 – 0.02032(waist, cm) – 0.09779(H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 23 publications
(30 reference statements)
3
66
0
Order By: Relevance
“…Insulin resistance is increased in youth with T1D compared to non-diabetic youth of similar age, sex, and BMIz, especially in children who fail to achieve target HbA1c levels (31,32). As insulin resistance increases so do cardiovascular disease risk factors (33). Similarly, data from the DCCT/EDIC Page 11 of 23 study in adults with T1D indicate that excessive weight gain is associated with insulin resistance, hypertension, dyslipidemia, central obesity, and more extensive atherosclerosis (as assessed by coronary artery calcium and carotid intima media thickness) (5).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is increased in youth with T1D compared to non-diabetic youth of similar age, sex, and BMIz, especially in children who fail to achieve target HbA1c levels (31,32). As insulin resistance increases so do cardiovascular disease risk factors (33). Similarly, data from the DCCT/EDIC Page 11 of 23 study in adults with T1D indicate that excessive weight gain is associated with insulin resistance, hypertension, dyslipidemia, central obesity, and more extensive atherosclerosis (as assessed by coronary artery calcium and carotid intima media thickness) (5).…”
Section: Discussionmentioning
confidence: 99%
“…Recent hyperinsulinemic-euglycemic clamp studies have shown that significant insulin resistance also exists in adolescents with T1D compared with age-, sex-, pubertal stage-, BMI and activity-matched controls (Nadeau et al, 2010). Using the same insulin sensitivity index used here, one study showed that nearly 33% of youth with T1D had insulin resistance (Specht et al, 2013). The mechanisms responsible for the association between insulin resistance and increased arterial stiffness in T1D are incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin sensitivity is recognized to play an important role in the development of vascular complications in type 1 diabetes (2, 38, 39), and SUA has been shown to predict both the development of albuminuria (4042) and progression of coronary artery calcification (19) in subjects with type 1 diabetes. In non-diabetic subjects and subjects with type 2 diabetes, there is a strong association between SUA and reduced insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%